CONTRIBUTION OF FINANCIAL LITERACY IN INCREATING THE USE OF FINANCIAL TECHNOLOGY - Marwan, Jubery (Universitas prof. Dr. Moestopo (Beragama), 2024)
This research was conducted on small and micro business actors (UKM) in Serang-Banten City with the aim of knowing the contribution and obtaining information on the benefits of financial literacy to create the use of financial technology mediated by financial self-efficacy and internal locus of control in business actors. Respondents were randomly selected to represent each particular commodity. Primary data is processed using a categorical Likert scale and statistical data analysis uses path analysis. The findings are that; 1) The benefits of financial literacy to build a high sense of trust and behave with strong self-control in managing one's finances; 2) The benefits of financial literacy to create a sense of self-confidence and strong self-controlled behavior and its impact on the use of financial technology both directly and indirectly. Most of them are familiar with banking access. They already have a strong sense of self-confidence and self-controlled behavior regarding understanding banking products and services, so they feel interested in understanding banking technology products and services. The impact of this research is expected to provide wiser alternative financial decisions.